Effect of a randomised 12-week resistance training programme on muscular strength, cross-sectional area and muscle quality in women having undergone Roux-en-Y gastric bypass. Issue 5 (4th March 2018) - Daniels, Paul; Burns, Ryan D.; Brusseau, Timothy A.; Hall, Morgan S.; Davidson, Lance; Adams, Ted D.; Eisenman, Patricia
ABSTRACT: The purpose of this study was to examine the effect of a 12-week resistance training programme on fat-free mass (FFM), muscle cross-sectional area, muscular strength and muscle quality in women who underwent Roux-en-Y gastric bypass surgery. Participants were 16 women (mean age = 44.9 ± 10.2 years) from bariatric surgical groups who were randomly assigned into either a control or an intervention group. Air displacement plethysmography measured FFM and magnetic resonance imaging measured quadriceps muscle cross-sectional area and whole thigh muscle cross-sectional area. Muscular strength and quality was assessed using an estimated 1-Repetition Maximum assessment. All measurements were collected twice, at baseline and at a 12-week follow-up. There were significantly greater improvements in leg press strength (mean differences = 55.4%, P  < 0.001, Cohen's d  = 2.4), leg extension strength (mean differences = 18.0%, P  = 0.014, Cohen's d  = 0.86) and leg press muscle quality (mean differences = 54.5%, P  < 0.001, Cohen's d  = 1.9) in the intervention group compared to the control group following the resistance training programme. The resistance training intervention significantly improved muscular strength and quality; however, it did not illicit changes in FFM or muscle cross-sectional area in women who underwent Roux-en-Y gastric bypass surgery.